THE BEST HARVESTERS ASSESSMENT SYSTEM AT PT. PADASA ENAM UTAMA BY SIMPLE ADDICTIVE WEIGHTING (SAW) METHOD - Trika Ayu Intan Sari; Nuriadi Manurung; Santoso (Jurnal Teknik Informatika (Jutif), 2022)
The selecting of best harvesters at PT. Padasa Enam Utama have been using a manual method so that the announcement of reward results is often delayed. The purpose of this research was application of the simple addictive weighting (SAW) method which has the opportunity to facilitate the management of PT. Padasa Enam Utama to determine the best harvester and make it easier to display reward results to employees. The research method was carried out using the SAW method with the research stages consisting of data collection, analysis, system design, system development. The results of this study that SAW value referring to the criteria for harvesters who deserve to receive rewards according to the relevant data. The results were namely 3 harvesters, Selamet, Agun, and Ateng with the highest SAW value were respectively 0.7647, 0.6235 and 0.5411. This study concluded that SAW method can help CQC (Crop Quality Control) in determining the best harvesters who deserved a reward.